Empirical prediction model of salt intrusion along Shatt Al-Arab River, southern Iraq - Al-Battat, Munaf Q. (Mesopotamian Journal of Marine Sciences, 2019)
In this paper the prediction of salt intrusion model along the Shatt Al-Arab River was applied.The analyses showed the result of salinity intrusion inShatt Al-Arab River which is a confluence of Tigris and Euphrates Rivers, is essential to present a holistic picture. The analyses were based on data of seven years (2005-2011) as well as full day tide during 2009 when the salinity rose to its highest level.Due to the decrease in the quantity of water releases reaching the River from it’s sources, the salinity of the saline water is increased with the flow decrease of fresh water. During the study period, the amount of flow was between 5-50 cubic meters per second. The salinity value fluctuated according to the flow reaching it’s highest level in 2009, when the discharge was 5m3/Sec. The field salinity at the studied stations: Al-Fao, Al-Seba, Al-Ashar and BinUmmerwere 32.2, 26, 11.7 and 1.4 ppt., respectively. However, salinity prediction model gives values of 32.44, 24.1, 13.4 and 2.9 ppt. for the four stations, respectively. But when the discharge was 50m3/Sec., the field salinity at these stations were 27.5, 2.2, 1.92 and 0.8 ppt., respectively, the salinity prediction model gives values of: 27, 2.28, 1.73 and 0.5 ppt. at the four stations, respectively. These results represent a good salinity prediction modelin the Shatt Al-Arab River.